Living in the Internet of Things: Cybersecurity of the IoT - 2018 2018
DOI: 10.1049/cp.2018.0009
|View full text |Cite
|
Sign up to set email alerts
|

Raising Awareness of IoT Sensor Deployments

Abstract: The IoT is increasingly being used to support smart spaces and physical analytics and yet much of this smartness is made deliberately invisible to the user-echoing Weiser's vision of calm computing and technology that fades into the background. However, this means that users may not be aware or may not understand how the IoT is being deployed in their area. In other domains we know that a lack of awareness and a lack of understanding can lead to poor user experience/frustration, mistrust, suspicion, inability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…One of these operation could be done with the support of other sciences such as brainwashing technic. By utilizing the Internet, nowadays you don't have to face to face to do brainwashing (Mikusz, 2018). IoT could be used as a tool to screen biographies of target operation who fits the leadership criteria.…”
Section: Internet Of Things In the Intelligence Recruitment Missionsmentioning
confidence: 99%
“…One of these operation could be done with the support of other sciences such as brainwashing technic. By utilizing the Internet, nowadays you don't have to face to face to do brainwashing (Mikusz, 2018). IoT could be used as a tool to screen biographies of target operation who fits the leadership criteria.…”
Section: Internet Of Things In the Intelligence Recruitment Missionsmentioning
confidence: 99%
“…In general, smart homeowners need to be aware of the potential threats in order to be motivated to configure their smart devices to match their privacy requirements [52], [94]. Several studies have shown that smart homeowners prefer to be aware of the data collected about them [57,76,80]. From another perspective, Tabassum et al [99] confirmed that smart homeowners were uncertain about how their data is used, and they expressed a wish for more transparency and control.…”
Section: Smart Home Privacy Concernsmentioning
confidence: 99%
“…An innovative design was the Bicycle Barometer [5] that visualized opinions collected by passers-by. Mikusz et al have also explored public awareness displays on IoT data [34]. These visualizations demonstrate that data can be successfully conveyed in public/urban environments.…”
Section: Public Data Visualizationsmentioning
confidence: 99%